2010
DOI: 10.1371/journal.pone.0010292
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence in Williams Syndrome Is Related to STX1A, Which Encodes a Component of the Presynaptic SNARE Complex

Abstract: Although genetics is the most significant known determinant of human intelligence, specific gene contributions remain largely unknown. To accelerate understanding in this area, we have taken a new approach by studying the relationship between quantitative gene expression and intelligence in a cohort of 65 patients with Williams Syndrome (WS), a neurodevelopmental disorder caused by a 1.5 Mb deletion on chromosome 7q11.23. We find that variation in the transcript levels of the brain gene STX1A correlates signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 41 publications
0
33
0
5
Order By: Relevance
“…The identification of clear association of duplications in this controlled study of ASD is particularly striking given that the reciprocal deletion results in a developmental syndrome characterized in part by an empathic, gregarious, and highly social personality (Pober, 2010). Moreover, several lines of evidence, including atypical deletions (Antonell et al, 2010), mouse models (Fujiwara et al, 2006; Hoogenraad et al, 2002; Meng et al, 2002; Sakurai et al, 2010), and gene expression x phenotype studies (Gao et al, 2010; Korenberg et al, 2000) have already identified CAPGLY domain containing linker protein 2 ( CLIP2 ), LIM domain kinase 1 ( LIMK1 ), General transcription factor II, i ( GTF2i ), and Syntaxin 1A ( STX1A ) as the leading candidates among the 22 genes within the region for involvement in the cognitive and social phenotypes. The characterization of this single region in which opposite changes in copy number contribute to contrasting social phenotypes promises to set the stage for a range of interesting studies of the role of gene dosage within this interval and the genesis of social mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of clear association of duplications in this controlled study of ASD is particularly striking given that the reciprocal deletion results in a developmental syndrome characterized in part by an empathic, gregarious, and highly social personality (Pober, 2010). Moreover, several lines of evidence, including atypical deletions (Antonell et al, 2010), mouse models (Fujiwara et al, 2006; Hoogenraad et al, 2002; Meng et al, 2002; Sakurai et al, 2010), and gene expression x phenotype studies (Gao et al, 2010; Korenberg et al, 2000) have already identified CAPGLY domain containing linker protein 2 ( CLIP2 ), LIM domain kinase 1 ( LIMK1 ), General transcription factor II, i ( GTF2i ), and Syntaxin 1A ( STX1A ) as the leading candidates among the 22 genes within the region for involvement in the cognitive and social phenotypes. The characterization of this single region in which opposite changes in copy number contribute to contrasting social phenotypes promises to set the stage for a range of interesting studies of the role of gene dosage within this interval and the genesis of social mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed COMT mRNA expression in 46 healthy individuals (14 Val/Val, 18 Val/Met, 14 Met/Met). MB-COMT (long transcript) and total-COMT (both long and short transcripts) mRNA levels were assessed using the comparative C T method with ␤-actin as reference (control) gene (Gao et al, 2010) (primers available on request). Real-time quantitative PCR was performed using ABI PRISM 7700 Sequence Detection System in combination with continuous SYBR Green detection (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, as a critical protein involved in the docking of synaptic vesicles and the regulation of Ca 2+ -dependent neurotransmitter release (Söllner et al 1993a,b), Stx1a has potential as a mediator of miR-132/-212's effects on cognition. Indeed, Stx1a is strongly implicated in the autism spectrum disorders (ASDs) and other cognitive disorders (Gao et al 2010b;Durdiaková et al 2014). An immunohistochemical analysis of STX1A expression within stratum oriens and stratum radiatum (two regions that exhibit robust levels of STX1A; Ruiz-Montasell et al 1996) revealed a marked increase in STX1A in cKO mice relative to control animals (Fig.…”
Section: Cognitive Impairment Following Targeted Deletion Of Mir-132/mentioning
confidence: 99%